Advances in Parallel, Distributed Computing First International Conference on Parallel, Distributed Computing Technologies and Applications, PDCTA 2011, Tirunelveli, Tamil Nadu, India, September 23-25, 2011, Proceedings - Nagamalai, Dhinaharan; Renault, Eric; Dhanuskodi, Murugan (Communications in Computer and Information Science,, 2011)
This book constitutes the refereed proceedings of the First International Conference on Advances in Parallel, Distributed Computing Technologies and Applications, PDCTA 2011, held in Tirunelveli, India, in September 2011. The 64 revised full papers were carefully reviewed and selected from over 400 submissions. Providing an excellent international forum for sharing knowledge and results in theory, methodology and applications of parallel, distributed computing the papers address all current issues in this field with special focus on algorithms and applications, computer networks, cyber trust and security, wireless networks, as well as mobile computing and bioinformatics.